A multicenter, randomized, phase III study comparing the efficacy and safety of follitropin alpha biosimilar and the original follitropin alpha. (October 2019) - Barakhoeva, Zarema; Vovk, Lyudmila; Fetisova, Yulia; Marilova, Nina; Ovchinnikova, Maria; Tischenko, Marina; Scherbatyuk, Yulia; Kolotovkina, Alexandra; Miskun, Anna; Kasyanova, Galina; Teterina, Tatyana; Zorina, Irina; et al.
Abstract: Objective: The aim of the present study was to investigate the therapeutic equivalence between the follitropin alpha biosimilar and the reference medication in women undergoing assisted reproductive technologies (ART). Study design: This multicenter, randomized (1:1), embryologist-blinded, parallel-group, comparative phase III study involved 110 women aged 20–35 years old with tubal and/or male factors of infertility. All of the subjects underwent controlled ovarian hyperstimulation (COH) using a gonadotropin-releasing hormone antagonist (GnRH-ant) protocol. Over the 5-day fixed-dose regimen, the women received 150 IU/day of follitropin alpha biosimilar (n = 55) or original follitropin alpha (n = 55), followed by dose adaptation. The primary endpoint for assessing the therapeutic equivalence was the number of retrieved oocytes using a pre-determined clinical equivalence margin of ± 3.4 oocytes. Results: Similar numbers of oocytes were retrieved in both groups: 12.16 ± 7.28 in the follitropin alpha biosimilar group and 11.62 ± 6.29 in the original follitropin alpha group, with mean difference of 0.546 ± 1.297 oocytes (95% confidence interval [CI]: -2.026, 3.116), p = 0.002 (intention-to-treat [ITT] population). Additionally, no statistically significant differences were found for secondary endpoints: the onset of biochemical (34.7% and 36.7%, p = 0.883), clinical pregnancy (26.5% and 32.7%, p = 0.507), delivery (26.5% and 24.5%, p = 0.817) and take-home baby rate (28.6% and 26.5%, p = 0.816) for the follitropin biosimilar and original follitropin groups (per-protocol [PP] population). Ovarian hyperstimulation syndrome was observed in subjects with a positive pregnancy test in 0% and 3.64% of cases and after triggering ovulation in 7.27% and 3.64% for the follitropin biosimilar and original follitropin groups, respectively. Conclusions: This study demonstrated similar therapeutic equivalence and safety profiles between the follitropin alpha biosimilar and the reference follitropin in women who underwent COH in GnRH-ant cycles. Trial registration number: 1. Name of the registry:ClinicalTrials.gov . Trial registration number: NCT03088137. Date of registration: 02.03.2017, retrospectively registered. Trial conducted between 08.02.2017 and 17.08.2018, the date of enrollment of the first participant – 08.02.2017. 2. Name of the registry: Russian Ministry of Health, grls.rosminzdrav.ru . Trial registration number: RCT 754. Date of registration: 26.10.2016, prospectively registered.